2022
DOI: 10.18316/sdh.v10i2.9009
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à higiene oral do paciente crítico com COVID-19

Abstract: Objetivo: O presente estudo teve como objetivo avaliar a higiene oral do paciente crítico com COVID-19 e fatores associados. Métodos: foi realizado um estudo transversal, que consta na avaliação da higiene oral de pacientes internados em UTI com COVID-19 sob uso de ventilação mecânica por meio do Índice de Higiene Oral Simplificado (IHO-S) e do Indicador de Higiene Oral do Paciente Crítico (IHOPC). Resultados: a amostra foi composta por 139 pacientes, sendo 59% do sexo masculino, 44,6% obesos, 93,5% com tubo o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The respondent was asked about the place of hospitalization, 14 of the 20 individuals were hospitalized in the public health network and 6 in the private network. Moreover, the hospitalization time of 40% of the individuals was less than 10 days, which concurs with Conceição's study, in which the time was around 6 days 8 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The respondent was asked about the place of hospitalization, 14 of the 20 individuals were hospitalized in the public health network and 6 in the private network. Moreover, the hospitalization time of 40% of the individuals was less than 10 days, which concurs with Conceição's study, in which the time was around 6 days 8 .…”
Section: Discussionsupporting
confidence: 90%
“…In this research, 50% of the interviewees reported needing ICU care. To assist in their survival, mechanisms such as orotracheal intubation and the use of invasive mechanical ventilation are used, which causes poor oral hygiene, increasing the risk of complications in the systemic health of the individual, such as ventilator-associated pneumonia 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation